Analysis of Limitations on the Design of a Small-Dimensional Robot for Investigating Damage to Panel Buildings - Karpenko, I. (ХНУРЕ, 2024)
The article analyzes the design limitations of a compact robot designed to investigate damage to panel houses. The requirements for size, maneuverability, energy efficiency, load capacity and the use of sensors to detect defects in hard-to-reach areas are considered. An approach to design optimization is proposed, taking into account operating conditions in a limited space, which allows to increase the efficiency of inspection and reduce the risks of destruction
Keywords: compact robot; panel houses; damage; structural limitations